Differentiation of Maize (Zea mays L.) from native wild grasses based on starch grain morphology. Cases from the Central Pampas of Argentina - Musaubach, María Gabriela (2013)
This paper presents, for the first time, a detailed study, from an archaeological perspective, of the morphological characteristics of the starch grains within the kernels of selected native wild grasses found in the Central Pampas of Argentina. We compared native wild grasses to maize starch grains, which can be distinguished from each other based on their size, shape and other attributes. The majority of the studied grains did not share morphological characteristics with maize starch grains. Considering this, it can be said that, if irregular and polyhedral grains with transverse or radial fissures dominate the starch assemblage, maize identification may be done on the basis of both morphology and size. Additionally, this research contributes to the characterization of the starch grains of the Panicoideae subfamily, which includes maize. Several classes of simple and compound starch grains are described and defined for native species of Pooideae, Chloridoideae, Arundinoideae, and Panicoideae subfamilies. The results obtained may constitute a baseline for the future determination of maize and wild grass use in archaeological contexts belonging to Middle/Late Holocene hunter-gatherers in the Pampas of Argentina and neighboring areas.